Pemanfaatan Residu Brem sebagai Bahan Substitusi Pembuatan “Arenia Sticky Rice” - Afri yanti (Jurnal Ilmiah Teknosains, 2017)
The aims of this research were to determine the proportion of brem residue as a substitute material of glutinous rice and the addition of palm sugar to the quality of Brem residue Dodol (Arenia Sticky Rice). This research used a Completely Randomized Design with two treatment factors, the combination of glutinous rice flour : brem residue (A) with three levels of treatment: A1 = 150: 50; A2 = 100: 100; A3 = 50: 150 and the percentage addition of palm sugar (B) with 3 levels of treatment: B1 = 75%; B2 = 100%; B3 = 125%. Each treatment was repeated twice to obtain 3 x 3 x 2 = 18 experimental units. Arenia Sticky Rice was analyzed the moisture, reducing sugar, texture and organoleptic. The combination between the proportion of glutinous rice flour : brem residue with the addition of palm sugar significantly affect to the product characteristics of Arenia sticky rice  both chemical, physical and organoleptic. Overall,  the proportion of glutinous rice flour : Brem residue (50: 150) with 125% palm sugar  produced less favored arenia sticky rice because of the hard texture, dark brown color, too sweet taste and strong aroma of tapai.